Malaysian Construction Self-Initiated Expatriate (SIE): Characteristics, Motivations And Repatriation Factors - Ishak, Norakmarwati (2018)
Self-initiated expatriates (SIE) are a sub-group of immigrant workforce in the study of international migration. They comprise of professionals, who on their own, initiated the migration process without depending on any organization. Their numbers are increasing and resulting in a brain drain of skilled workforce from the nation. Previous studies have indicated difficulties in identifying specific features of this subgroup and separating the SIE as an entity outside of the international migration theory. Previous studies on SIE have focused on career management and personal orientation of individuals and the studies were fragmented.